International Ratings: Statistical Aspects of Computing and Application. Part 1. Index of Economic Freedom and Global Competitiveness Index - Yerina, A. M. (Statistics of Ukraine, 2016)
Use of ratings as analytical tools for finding out competitive advantages of global economic actors has been increasingly important in the globalizing economic area, accelerating processes of international integration and the growing interdependence of countries. International ranks are an important source of information on capacities and performance of counties. Ranks, highlighting strong and weak sides effecting the country’s position in the global system of coordinates, are an indicator of the need for measures to eliminate shortcomings or broaden opportunities for enhancing competitive advantages. Rating algorithms differ by set of key indicators included in a rating system and aggregation method. A rating algorithm is realized in several consecutive phases. The most complicated phases in the statistical methodology context are: unification of scales for estimation of key indicators; and justification of algorithms for information compression at all the hierarchical levels of a rating system. The article is focused on methodological aspects for estimation of Index of Economic Freedom (IEF) and Global Competitiveness Index (GCI): structure of rating system, estimation scales and unification of key indicators, algorithms for compression of estimates and their analytical capacities. By IEF rank, countries are divided into five categories: from free to oppressed ones. Studies at the global level show direct correlation between economic freedom and high economic performance of countries. By Index of Economic Freedom - 2016, Ukraine has 162nd position with 46.8 scores. Of the ten components of economic freedom, Ukraine has high scores only in three: trade, fiscal and monetary freedom. The strongest negative impact on the Ukraine’s rank comes from unfavorable investment climate, weak protection of property rights, weak freedom from corruption, weak fiscal freedom and large government spending. By Global Competitiveness Index - 2016, Ukraine has 79th position with 4.03 scores. Ukraine lags far behind by factors like institutional environment, macroeconomic stability, effectiveness of financial and commodity markets, quality of national business climate, technological development. Ukraine still keeps relatively high positions in education system and size of domestic market. It follows that the government’s effort need to be focused on stabilization of public finances, recovering of bank system, setting up business friendly environment, which will enable for implementing the existing innovation and human capacities and lay the ground for gradual growth of international competitiveness of Ukraine and adaptation of the domestic economy for global transformations.